O2-S3.01 Feasibility and acceptability of self-sampling for rectal sexually transmitted infections (STI) among bisexual men in the USA. (10th July 2011) - Dodge, B; Van Der Pol, B; Reece, M; Malebranche, D; Fortenberry, D
Abstract : Introduction: Rectal sexually transmitted infections (STI) are a common health concern for men who have sex with men (MSM). Studies have not yet determined the relevance of these pathogens among men who have sex with both men and women (MSMW). Screening for rectal STI is not currently a widespread option for bisexual men in the USA. Methods: Qualitative data and self-obtained rectal specimens were collected from a diverse sample of bisexual men. Upon completion of the rectal self-sampling, each participant provided information regarding their overall experience with the process. Results: From a total sample of 75 bisexual men, 58 participants provided self-obtained rectal samples. While most men did not test positive, a prevalence (10.3%) of C. trachomoatis infection was found in this sample. Men who collected samples reported overall acceptability and comfort with self-sampling for rectal STI. Privacy was a primary concern for men regarding self-sampling. Of the men who did not provide a rectal self-sample, the most common reason was having been tested in the recent past. Discussion: Self-sampling is a feasible and acceptable option when offered to bisexual men. Research and interventions are needed to ascertain which combinations of STI testing (including self-sampling) and treatment methods are most appropriate for diverse groups of bisexual men.